IRF7: role and regulation in immunity and autoimmunity - Ma, Wei; Huang, Gang; Wang, Zhi; Wang, Li; Gao, Qiangguo (Frontiers in Immunology, 2023)
Interferon regulatory factor (IRF) 7 was originally identified as master transcriptional factor that produced IFN-Ⅰ and regulated innate immune response, subsequent studies have revealed that IRF7 performs a multifaceted and versatile functions in multiple biological processes. In this review, we provide a comprehensive overview on the current knowledge of the role of IRF7 in immunity and autoimmunity. We focus on the latest regulatory mechanisms of IRF7 in IFN-I, including signaling pathways, transcription, translation, and post-translational levels, the dimerization and nuclear translocation, and the role of IRF7 in IFN-III and COVID-19. In addition to antiviral immunity, we also discuss the role and mechanism of IRF7 in autoimmunity, and the further research will expand our understanding of IRF7.